Scoping response system management of alcohol's harm to others in lower middle income countries - Laslett, Anne-Marie; Waleewong, O.; Obot, I.; Benegal, V.; Hettige, S.; Florenzano, R.; Hanh, H.; Hanh, V.; Rao, G.; Room, R. (2016)
AIMS - As part of the WHO Harm from others' drinking project, Thailand, Sri Lanka, India, Chile, Nigeria and Vietnam undertook scoping studies to examine: which service agencies in low and middle income countries responded to people affected by others' drinking; how commonly key informants from these agencies indicated alcohol was part of the problems they managed; and whether any routine reporting systems collected information on alcohol's harm to others (AHTO) and the types and examples of harms experienced across the six countries. METHODS - Researchers synthetised within country peer-review literature, reports, news and agency website information. Additionally, researchers interviewed key informants to investigate current structures, functions and practices of service agencies, and in particular their recording practices surrounding cases involving others' drinking. RESULTS - 111 key informants agreed to participate from 91 purposively selected agencies from health, social protection, justice and police, and 'other' sectors. National and provincial level data, as well as state-run and civil society agency data were collected. Diverse service response systems managed AHTO in the different countries. A large range in the percentage of all cases attributed to AHTO was identified. Case story examples from each country illustrate the different responses to, and the nature of, many severe problems experienced because of others' drinking. CONCLUSIONS - AHTO was a major issue for service systems in LMIC, and significantly contributed to their workload, yet, very few recording systems routinely collected AHTO data. Recommendations are outlined to improve AHTO data collection across multiple sectors and enable LMIC to better identify and respond to AHTO.